2000
DOI: 10.1124/mol.58.6.1213
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphatase Inhibitors Selectively Antagonize β-Adrenergic Receptor-Dependent Regulation of Cardiac Ion Channels

Abstract: ␤-Adrenergic receptor stimulation regulates the activity of several different cardiac ion channels through an adenylate cyclase/cAMP/protein kinase A-dependent mechanism. Previous work has suggested that basal tyrosine kinase activity attenuates the ␤-adrenergic responsiveness of these cardiac ion channels, supporting the idea that tyrosine phosphorylation exerts an inhibitory effect at some point in the common signaling pathway. To determine which element in the ␤-adrenergic pathway is regulated by tyrosine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
2
13
1
Order By: Relevance
“…We previously demonstrated that genistein, a tyrosine kinase inhibitor, can increase the sensitivity of cardiac ion channels to b 1 -AR stimulation, suggesting that basal tyrosine kinase activity inhibits badrenergic responsiveness in cardiac myocytes (Hool et al, 1998). Consistent with this idea, we found that vanadate derivatives that inhibit tyrosine phosphatase activity can also inhibit b-adrenergic responses, including b-adrenergic stimulation of the L-type Ca 2 þ current (I Ca-L ) (Sims et al, 2000;Belevych et al, 2001). Vanadate can act as a phosphate analog, binding to and inhibiting phosphoryl transfer enzymes like tyrosine phosphatases (Shaver et al, 1995).…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…We previously demonstrated that genistein, a tyrosine kinase inhibitor, can increase the sensitivity of cardiac ion channels to b 1 -AR stimulation, suggesting that basal tyrosine kinase activity inhibits badrenergic responsiveness in cardiac myocytes (Hool et al, 1998). Consistent with this idea, we found that vanadate derivatives that inhibit tyrosine phosphatase activity can also inhibit b-adrenergic responses, including b-adrenergic stimulation of the L-type Ca 2 þ current (I Ca-L ) (Sims et al, 2000;Belevych et al, 2001). Vanadate can act as a phosphate analog, binding to and inhibiting phosphoryl transfer enzymes like tyrosine phosphatases (Shaver et al, 1995).…”
Section: Introductionsupporting
confidence: 71%
“…Previous studies have demonstrated that the inhibition of tyrosine phosphatase activity by vanadate derivatives has little or no effect on the basal L-type Ca 2 þ current in cardiac myocytes (Wang & Lipsius, 1998;Ogura et al, 1999;Sims et al, 2000;Belevych et al, 2001). On the other hand, inhibition of tyrosine phosphatase activity by PAO, an arsenicbased compound, has been reported to regulate the basal L-type Ca 2 þ channel activity in vascular smooth muscle cells and neurons (Pafford et al, 1995;Wijetunge et al, 1998).…”
Section: Pao Transiently Stimulates the Basal L-type Ca 2 þ Channel Amentioning
confidence: 99%
See 1 more Smart Citation
“…Myocytes were superfused with 1 M bpV(phen) for 5 min before the effects of 40 M genistein or equol in the continuing presence of 1 M bpV(phen) were determined. One hundred micromolar bpV(phen) has been reported to have no significant effect on I Ca,L in guinea pig ventricular myocytes (Sims et al, 2000), although we found that this concentration of bpV(phen) markedly decreased cell shortening. We therefore chose to use a concentration of 1 M bpV(phen), which has been shown to be effective in inhibiting PTP in cultured hepatoma cells (Posner et al, 1994).…”
contrasting
confidence: 54%
“…Several effects of isoproterenol on β-adrenergic receptor bearing cells have been antagonised by sodium orthovanadate mainly due to its proteintyrosine phosphatase inhibitory properties (Hudgins and Bond, 1979;Nieder et al, 1979;Churchill and Churchill, 1982;D'Ocon, 1989;Gordon, 1991;Sims et al, 2000). Due to the insulin-like effects of VO 4 , it can antagonise the effects of ISO on lipolysis (Mooney et al, 1989;Li et al, 1997;Castan et al, 1999) as well.…”
mentioning
confidence: 99%